A NEW APPROACH TO REHABILITATION OF JUVENILES WITH RECURRENT RESPIRATORY INFECTIONS - O.I. Pikuza; D.I. Sadykova; E.V. Generalova (Вопросы современной педиатрии, 2007)
The article gives the efficiency findings of tonsilgon n phytomedication within rehabilitation of juveniles with recurrent respiratory infections. Medication efficiency was appraised by the noninvasive methods of the registration as to the colonization resistance of the oral cavity. It is demonstrated that the application of the phytomedication effectively restores the reserves of the mucosal protection held by the oral cavity, reduces the recurrence of the acute respiratory diseases. The medication is well tolerated and may be recommended for the application as a part of the sanitary actions in the given group of the patients. Key words: adolescent, recurrent respiratory infections, colonization resistance, rehabilitation, phytotherapy.